Implementation of the ASEAN Agreement on Transboundary Haze Pollution in the Southeast Asia Region - Itasari, Endah Rantau; Mangku, Dewa Gede Sudika (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to determine the extent of the implementation of the ASEAN Agreement on Transboundary Haze Pollution in the Southeast Asia Region. This study was normative empirical legal research (applied law research). Empirical normative legal research began with written positive legal provisions that were applied to in-concreto legal events in society. The principle of the working mechanism of the ASEAN Agreement on Transboundary Haze Pollution was the right to exploit one’s own resources with environmental and development policies, but this cannot be separated from the responsibility to ensure that exploitative activities did not cause environmental damage and threaten human health from other countries or an area outside the jurisdiction of a country but seeing the incidence every year there were still forest fires that cause a large haze and cause inconvenience to other ASEAN member countries and this must be immediately sought out so that an agreement that had been mutually agreed upon the same can be a parameter to reduce the occurrence of haze in the Southeast Asia region.